2012
DOI: 10.3892/mmr.2012.1099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SASH1 on melanoma cell proliferation and apoptosis in vitro

Abstract: Abstract. The SAM and SH3 domain containing 1 (SASH1) gene was originally identified as a potential tumor suppressor gene in breast cancer, mapped on chromosome 6q24.3. The expression of SASH1 plays a prognostic role in human colon cancer. Its expression is frequently downregulated in several human malignancies. However, the biological function of SASH1 in melanoma cells is yet to be determined. In this study, in order to investigate the tumor suppressive effects of the SASH1 gene, an A-375 stable melanoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(34 reference statements)
4
27
0
1
Order By: Relevance
“…6,7 Consistent with the onset of carcinoma in the affected individuals in this study, SASH1 was recently reported to be involved in the tumorigenesis of several cancers. [15][16][17][18][19][20] Cellular experiments showed that SASH1 localizes to the nucleus and cytoplasm of epithelial cells and might regulate cellular migration and adhesion, through its role in protruding membrane structures. 21 Through its central SH3 domain, SASH1 interacts with the actin cytoskeleton and especially cortactin, a major regulator of actin filament dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Consistent with the onset of carcinoma in the affected individuals in this study, SASH1 was recently reported to be involved in the tumorigenesis of several cancers. [15][16][17][18][19][20] Cellular experiments showed that SASH1 localizes to the nucleus and cytoplasm of epithelial cells and might regulate cellular migration and adhesion, through its role in protruding membrane structures. 21 Through its central SH3 domain, SASH1 interacts with the actin cytoskeleton and especially cortactin, a major regulator of actin filament dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…SASH1 encodes a candidate tumor suppressor from the SLY family of signal proteins. [15][16][17][18][19][20] This variant was absent from Exome Variant Server, dbSNP and local exomes, predicted as deleterious by Condel and possibly damaging by Polyphen2, and comes from a well-conserved sequence (GERP conservation score: 5090) (see Web Resources). Cosegregation analysis in all available relatives confirmed its presence in a homozygous state in both affected patients (III.6 and III.3), in a heterozygous state in both parents and an unaffected brother (III7) and absent in the unaffected sister (III4).…”
Section: Genetic Investigationsmentioning
confidence: 99%
“…Recent studies from 2012 focusing on SASH1 function in cancer, 107,108,109,110 showed that SASH1 over-expression in different cancer cell lines lead to accumulation of cells in G0/G1 phase, indicating an inhibitory effect of SASH1 on cell proliferation. Accordingly, cyclin D1 levels were found lowered in all but one cell line and cell invasiveness in vitro assays showed that SASH1 overexpression lead to decreased invasiveness of the cancerous cells.…”
Section: Sash1 In Cancermentioning
confidence: 99%
“…These results indicated that the down-regulation of SASH1 is at least in part due to gene deletion (13). Down-regulation of SASH1 expression was closely correlated with tumor invasion, metastasis, and poor prognosis (22)(23)(24). However, the specific role of SASH1 in ovarian carcinoma has not yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 57%
“…SASH1 has been suggested as a candidate tumor suppressor. The reduction or absence SASH1 is closely related to tumor growth, invasion, metastasis, and poor prognosis (13,14,23,24). Zeller et al (13) reported that SASH1 mRNA expression was significantly reduced or completely absent in 6 breast cancer cell lines, and that it was also significantly decreased in primary thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%